Spectrophotometry and electrical conductivity studies of multiwall nanotubes dispersed in nematic liquid crystals - Lisetski, L.N.; Lebovka, N.I.; Sidletskiy, O.Ts.; Panikarskaya, V.D.; Kasian, N.A.; Kositsyn, S.S.; Lisunova, M.O.; Melezhyk, O.V. (Functional Materials, 2007)
Optical transmission and electric conductivity were measured as a function of temperature for thin layers of multiwall nanotubes (MWNTs) dispersed in a mixture of cyanobiphenyl nematic liquid crystals (LC) ZhK-1282. At MWNT concentrations of 0.01-0.15 wt. % , characteristic changes in transmission at the nematic-isotropic phase transition temperature evidence that MWNTs integrate into LC matrix in a manner similar to that of the conventional non-mesogenic dopants. The electrical conductivity shows a percolation-like behaviour at ultra-low MWNTs loading of LC matrix below concentration levels of ~0.01 wt. % , which reflects the high aspect ratio of the conductive filler and the existence of strong interactions between LC matrix and MWNTs.